1997
DOI: 10.1073/pnas.94.7.3235
|View full text |Cite
|
Sign up to set email alerts
|

Regular alcohol consumption mimics cardiac preconditioning by protecting against ischemia–reperfusion injury

Abstract: Epidemiologic studies indicate that longterm alcohol consumption decreases the incidence of coronary disease and may improve outcome after myocardial infarction. Attenuation of ischemia-reperfusion injury after myocardial infarction improves survival. This study investigates the possibility that alcohol consumption can improve survival after myocardial infarction by reducing ischemia-reperfusion injury. Hearts were isolated from guinea pigs after drinking ethanol for 3-12 weeks and subjected to global ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 37 publications
(58 reference statements)
3
68
1
Order By: Relevance
“…Male Hartley guinea pigs (275-300 g; n ϭ 9 ethanol; n ϭ 9 control) were given 10% (a dose more consistent with moderate consumption) or 0% ethanol and solid food ad libitum (Lab Diet: PMI Feeds, St. Louis) for 8 wk as described previously (14). Isolated hearts were perfused for 10 min with Krebs-Henseleit perfusate (pH 7.4, 37°C) bubbled with 95%O 2 /5%CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Male Hartley guinea pigs (275-300 g; n ϭ 9 ethanol; n ϭ 9 control) were given 10% (a dose more consistent with moderate consumption) or 0% ethanol and solid food ad libitum (Lab Diet: PMI Feeds, St. Louis) for 8 wk as described previously (14). Isolated hearts were perfused for 10 min with Krebs-Henseleit perfusate (pH 7.4, 37°C) bubbled with 95%O 2 /5%CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The increasing use of emergent reperfusion therapies during acute MI, including thrombolysis and coronary angioplasty, provides impetus for finding therapies to reduce ischemia-reperfusion injury. We recently found that regular ethanol consumption induces long-term protection against ischemia-reperfusion injury in guinea pig hearts (14). We showed that this cardioprotective effect of ethanol requires adenosine A 1 receptor activation at the time of ischemia (14), like experimental ischemic preconditioning (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,118] Ischemic preconditioning (IPC) is the most potent form of endogenous myocardial protection against irreversible ischemia-reperfusion injury. In an animal models, longterm alcohol consumption reduced myocardial ischemia-reperfusion injury possibly through repeated myocyte adenosine receptor activation, [119] and sustained translocation of epsilon protein kinase C (εPKC). [120] In situ studies in rabbit showed, ethanol exposure followed by washout or sufficient time to metabolize the alcohol prior to ischemia, induces preconditioning-like myocardial protection.…”
Section: Alcohol Preconditioningmentioning
confidence: 99%